Potent and selective TYK2-JH1 inhibitors highly efficacious in rodent model of psoriasis. (1st October 2022) - Leit, Silvana; Greenwood, Jeremy R.; Mondal, Sayan; Carriero, Samantha; Dahlgren, Markus; Harriman, Geraldine C.; Kennedy-Smith, Joshua J.; Kapeller, Rosana; Lawson, Jon P.; Romero, Donna L.; Toms, Angela V.; Shelley, Mee; et al.
Graphical abstract: Abstract: TYK2 is a member of the JAK family of kinases and a key mediator of IL-12, IL-23, and type I interferon signaling. These cytokines have been implicated in the pathogenesis of multiple inflammatory and autoimmune diseases such as psoriasis, rheumatoid arthritis, lupus, and inflammatory bowel diseases. Supported by compelling data from human genetic association studies, TYK2 inhibition is an attractive therapeutic strategy for these diseases. Herein, we report the discovery of a series of highly selective catalytic site TYK2 inhibitors designed using FEP+ and structurally enabled design starting from a virtual screen hit. We highlight the structure-based optimization to identify a lead candidate 30, a potent cellular TYK2 inhibitor with excellent selectivity, pharmacokinetic properties, and in vivo efficacy in a mouse psoriasis model.